Suggestions for Pension Re-Reform in Peru - Mesa-Lago, Carmelo (2016)
This essay proposes the need for an integral re-reform of the Peru pensionsystem, preceded by broad social dialogue, in order to overcome this system’smajor flaws. As well as a comprehensive model of re-reform, it recommendsspecific measures that: extend the low level of coverage of the labor forceand the elderly, expand Pensión 65, guarantee the minimum pension, improvebenefits, unify the national and private pension systems, increase competitionand reduce the high administrative costs and profits of private pension funds(AFP), create a public AFP, strengthen financial and actuarial sustainability, raisecapital returns, and shift the disability-survivors premium to employers. Thisproposal also favors mandatory rather than voluntary affiliation to the AFP.